Pembelajaran Tari Tradisional Banten Untuk Meningkatkan Keterampilan Siswa Kelas VII Di SMP Negeri 04 Kota Serang - jao, Siti Jaoharotul Kholishoh (Jurnal Pendidikan Tari, 2024)
The aim of learning dance is to develop sensory perception through various creative artistic experiences according to the character and stage of development of students' abilities at each level of education. The method used in this research is descriptive qualitative research, namely with the aim of explaining and providing an overview of events in the field, using the approach used in the research, namely the art education approach and Art in Education (AiE). Learning the art of traditional dance for class VII C students at State Junior High School 04, Serang City, is able to provide a meaningful and holistic experience in accordance with the competency demands in the 2013 (K-13) curriculum because the dance contains many meanings, starting from how to appreciate someone, and proves that people can still live in harmony, despite the diversity and differences that exist in Banten.